3-D numerical modelling and experimental investigation of coupled photovoltaic thermal and flat plate collector. (August 2021) - Chandan,; Suresh, V.; Iqbal, S.Md.; Reddy, K.S.; Pesala, Bala
Highlights: A 3-D numerical model for coupled PVT and FPC system has been developed. A close match between simulation and experiments is observed with relative error under 5% The experiment conducted on PVT -FPC system at 30LPH showed outlet water temperature of 63–67 °C. Thermal and electrical efficiency from the glazed PVT collector is observed to be 35% and 10.3%, respectively. Thermal and electrical efficiency from the unglazed PVT collector is observed to be 25% and 16%, respectively. Abstract: Photovoltaic Thermal (PVT) systems generate hot water and electricity simultaneously. The grade of thermal energy generated by such PVT systems is low, resulting in limited application. To overcome this challenge, the coupling of the PVT system to a secondary flat plate collector (FPC) has been explored in this work. For the system's performance estimation, a 3-D numerical model has been developed for both glazed and unglazed PVT-FPC collector. Based on the numerical model, PVT collectors have been fabricated, and each is then connected in series to a commercially available FPC collector. Experiments conducted on the fabricated PVT-FPC system showed a close match between simulation and experiments. Further, experiments conducted on the unglazed PVT – FPC collector showed a peak outlet water temperature of 60–63 °C at 30 LPH. For the unglazed PVT collector, the peak electrical and thermal efficiency of 16% and 25% is reported respectively, whereas for the FPC collector, the thermal efficiency of 35% is reported. Compared to an individual unglazed PVT collector, 17 °C higher outlet water temperature is reported for the coupled system. Similarly, for the case of glazed PVT-FPC collector, the peak outlet water temperature reported is 65–67 °C at 30 LPH with 14–15 °C higher outlet water temperature.